The Position of Indegenous People in the Culture and Tourism Developments: Comparing Indonesia and East Timor Tourism Laws and Policies (Journal of Indonesian Legal Studies, 2022)
The expansion of development brings many impacts, including in the discourse of indigenous peoples in the midst of tourism development. On the one hand, culture and indigenous peoples are the main pillars in the use of culture-based tourism such as in Bali, Indonesia, but on the other hand, tourism development raises questions about legal protection for indigenous peoples. This study aims to analyze and compare various laws and policies in tourism development in Bali (Indonesia) and Atauro (Timor Leste) and the position of indigenous peoples in the midst of various tourism policies. By comparing several related policies, this research found and confirmed that existing cultural arrangements were limited to the cultural identity of indigenous peoples and as a tourist attraction for Indonesia, but there are no regulations that give a definition of culture as an economic resource. In Timor Leste, Ecotourism management in Beloi Village is still far from the plan. The government as policy makers and facilitators impressed walk alone in terms of management tourist.